0899 Long-term Effects Of Adenotonsillectomy In Children Diagnosed With Obstructive Sleep Apnea On Risk Factors For Cardiovascular Morbidity. (27th May 2020) - Even Tsur, J; Auhasira, R; Shiloh, A; Novack, V; Goldbart, A
Abstract: Introduction: Obstructive sleep apnea (OSA) is an independent risk factor for cardiovascular morbidity in adults. In children, cardiovascular morbidity associated with OSA is usually thought to resolve after tonsillectomy and adenoidectomy (T&A). There is no information regarding the long term effects of T&A on future cardiovascular morbidity in children diagnosed with OSA. In this study, we performed data mining to assess long-term effects of adenotonsillectomy on risk factors for cardiovascular disease, in young adults. Methods: This study retrospectively investigated the population defined by a previous study in our institution [Tarasiuk etal Pediatrics 2004] and compared a group of children diagnosed with OSA and underwent T&A(n=130) to a group of children diagnosed with OSA that did not undergo T&A(n=90) to a control group without OSA (n=505). Demographic data, vital signs, anthropometric measurements, medical diagnoses (9th revision (ICD-9) codes) and medication purchases were captured from the HMO computerized database, between the years 1998-2018. When appropriate, univariate comparisons were made using χ  2 -test or Fisher's exact test for categorical variables, and one-way ANOVA or Kruskal-Wallis tests for quantitative variables. We performed multivariate logistic regression to model the factors associated with the diagnosis of obesity. IBM SPSS software, version 25.0, was used for statistical analysis. Results: We have found that 20 years after their OSA diagnosis, patients (25.1 years, 52.2% males, 26.2 BMI) who were diagnosed with OSA at age 5 and did not undergo T&A consumed more medications associated with cardiovascular morbidity (anti-hypertensive, statins, aspirin) than those who underwent T&A(P<0.001). Surprisingly, multivariate logistic regression revealed that only females diagnosed with OSA (with or without T&A) were diagnosed as obese in comparison to those that did not have OSA (P<0.001). Conclusion: Children who were diagnosed with OSA and were not operated will consume more medications (anti-hypertensive, anti-hyperlipidemia, aspirin) as young adults, a surrogate marker for early cardiovascular disease. OSA in girls seems to serve as a risk factor for obesity in their third decade of life. It is important to diagnose and treat OSA in children, and to monitor and prevent obesity, mainly in females. Support: Israel Science Foundation (ISF) 1344/15